A Proposal for Clustering the Dimensions of National Culture. (May 2014) - Maleki, Ammar; de Jong, Martin
Since Hofstede introduced his approach to understanding cultural differences through dimensions of national culture, various authors have presented their own dimensions, sometimes similar, sometimes different, and sometimes partially overlapping. The status quo in the development of research on cultural dimensions can now be qualified by two words: enriched and messy. Some scholars have attempted to bring the most likely common denominators of the dimensions together in an overview, but these attempts were based on ad hoc considerations and common sense. The goal of this article is to come to a synthesis of the insights from relevant authors and present a set of clusters of cultural dimensions based on systematic theoretical and statistical analysis. This is done by testing the conceptually established clusters through an ecological factor analysis. We included the work produced by Hofstede, Inglehart, Schwartz, GLOBE (Global Leadership and Organizational Behavior Effectiveness), Minkov, and a number of well-known qualitative authors, ending up with nine exclusive clusters: Individualism versus Collectivism, Power Distance, Uncertainty Avoidance (UA), Mastery versus Harmony, Traditionalism versus Secularism, Indulgence versus Restraint, Assertiveness versus Tenderness, Gender Egalitarianism, and Collaborativeness.